Systematization of ergonomic and inclusive principles for designing interiors of autonomous vehicles - Asistent Prof. Elena Angeleska PhD., Prof. Sofija Sidorenko PhD., Aleksandar Jankovic MSc., Ass. Prof. Tasko Rizov PhD., Aleksandra Aleksovska MSc., Ass.Prof. Nikola Avramov PhD. (University of Nis - Faculty of mechanical engineering, 2021)
The use of authonomous vehicles (AVs) offers possibilities for providing improved passenger experience and comfort as well as independent travel for persons with different types of impairments. This paper provides an analysis of ergonomic principles related with vehicle interiors, as well as principles of inclusion. This is done with the goal to withdraw key recommendations that need to be applied in the design process. Those recommendations are systematized as a list divided in several categories and organized in a manner that is easily understood and applicable in the vehicle interior development. In addition, this paper presents the design process of a self-driving shuttle interior in order to illustrate the practical application of the provided lists of ergonomic and inclusive principles and highlight their importance.
Keywords: ergonomics, inclusive design, human-centred design, autonomous vehicles, vehicle interior design